Career Development On Employee Performance - Purnama, Chamdan (Yayasan Pendidikan Belajar Berdikari, 2024)
Performance evaluation is a mechanism used to assess workers so that historical data can be compared. This study attempts to examine how employee performance is affected by work commitment, remuneration, and career growth. The sample method used in this study was random sampling with the Slovin formula to acquire 55 samples, and the population consisted of 214 employees of PT. Phase Delta Control Surabaya. The basic data will next be evaluated utilizing multiple linear regression analysis techniques provided by the SPSS application tool in order to confirm the research hypothesis. The study's findings demonstrate that career advancement, pay, and work dedication all have a favorable and substantial impact on employees' performance. At PT. Phase Delta Control Surabaya, career development, remuneration, and work dedication all have a good and significant impact on employee performance, at least in part.